1995
DOI: 10.1093/carcin/16.10.2327
|View full text |Cite
|
Sign up to set email alerts
|

The expression of placental-type glutathione S-transferase (GST-π) in human cutaneous carcinoma in situ, that is, actinic keratosis and Bowen's disease, compared with normal human skin

Abstract: The expression of human placental type glutathione S-transferase (GST-pi) was investigated in human cutaneous carcinoma in situ, that is, actinic keratosis and Bowen's disease, and compared with that in normal skin, using Northern blot and immunohistochemical analysis. In Northern blot examination, the expression of GST-pi transcript was recognized in all instances. Carcinoma in situ showed significantly higher expressions of GST-pi than normal skin. In the immunohistochemical examination, nuclear staining of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, nuclear localization has been recognized. Nuclear expression of GSTP has been reported in normal epithelium of esophagus (van Lieshout et al 1999) and cervix (Randall et al 1990) and in neoplastic lesions of skin (Shimizu et al 1995), cervix (Randall et al 1990), esophagus (van Lieshout et al 1999), mouth (Zhang et al 1998), and gliomas (Ali-Osman et al 1997). Nuclear expression of a theta class GST (GSTT) has also been observed in hepatocytes and bile duct cells (Quondamatteo et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, nuclear localization has been recognized. Nuclear expression of GSTP has been reported in normal epithelium of esophagus (van Lieshout et al 1999) and cervix (Randall et al 1990) and in neoplastic lesions of skin (Shimizu et al 1995), cervix (Randall et al 1990), esophagus (van Lieshout et al 1999), mouth (Zhang et al 1998), and gliomas (Ali-Osman et al 1997). Nuclear expression of a theta class GST (GSTT) has also been observed in hepatocytes and bile duct cells (Quondamatteo et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to benign lesion and mild to moderate dysplasia, the cases of severe dysplasia, CIS and SCC showed a tendency to nuclear and/or basal cell staining. Nuclear staining of GST-π has already been previously reported in premalignant lesions of human oral mucosa [34] and skin [22]. Its presence has been related to the malignant transformation and progression in transitional cell carcinoma [30].…”
Section: Discussionmentioning
confidence: 71%
“…Several studies in rat models of chemical liver carcinogenesis have showed that the π-class GST (the placental form) is induced in preneoplastic hepatocytic foci and may be used as a marker for preneoplastic and neoplastic lesions [6,14,19,20]. It has thus been proposed that the π-class might be a useful marker for the detection of preneoplastic and neoplastic cells in humans, and increased GST-π expression has been found in a wide variety of human tumours [4,10,16,17,22,23,31].…”
Section: Introductionmentioning
confidence: 99%